Perfluorooctane sulfonic acid (PFOS) adsorbed to polyethylene microplastics: accumulation and ecotoxicological effects in the clam Scrobicularia plana - Islam, Naimul (2021)
Microplastics are widespread in the marine environment, whereby organisms’ uptake these tiny particles, presenting adverse biological responses. Plastic debris also act as a vector of many contaminants which intensify their effects to marine organisms that depend on type, size, shape and chemical properties. This study aimed to assess the accumulation and potential toxicity of different sizes of microplastics with and without adsorbed perfluorooctane sulfonic acid (PFOS) in the clam Scrobicularia plana. Clams were exposed to 1 mg L-1 of virgin and PFOS (70.2 ± 12.4 μg g−1) contaminated lowdensity polyethylene microplastics of two different sizes (4-6 and 20-25 μm) over 14 days. Microplastic and PFOS accumulation and filtration rate were determined along with a multi biomarker approach to access the biological effects of microplastics accumulation. Biomarkers include oxidative stress (superoxide dismutase, catalase, glutathione peroxidases), biotransformation enzymes (glutathione-S-transferases) activity, neurotoxicity (acetylcholinesterase activity), oxidative damage and apoptosis. Microplastics and PFOS accumulated were microplastic size dependent but not PFOS dependent and filtration rate was reduced at the end of the exposure. Reactive oxygen species in gills and digestive gland were generated as a result of exposure to both types of microplastics, confirming the disturbance of the antioxidant system. Larger microparticles lead to stronger impacts, when compared to smaller ones which was also supported by Integrated Biomarker Responses index calculated for both tissues. An anti-apoptotic response was detected in digestive glands under exposure to any of the MPs treatments as a probable mechanism associated to carcinogenic responses derived from MPs uptake.